Stereotactic body radiation therapy using a respiratory-gated volumetric-modulated arc therapy technique for small hepatocellular carcinoma - Jeong, Yuri (BMC Cancer, 2018)
BACKGROUND: Volumetric-modulated arc therapy (VMAT) is a highly sophisticated linear accelerator-based treatment method, and allows dose rate-changing intensity modulation with gantry rotation. We report our clinical experiences with stereotactic body radiation therapy (SBRT) using a respiratory-gated VMAT technique for patients with hepatocellular carcinoma (HCC) when established curative treatments cannot be applied. METHODS: A total of 119 patients (139 lesions) with HCC who were treated with SBRT were registered between March 2012 and July 2013 at our institution. A dose of 10–15 Gy per fraction was applied over 3–4 consecutive days, resulting in a total dose of 30–60 Gy. RESULTS: The median follow-up period was 25.8 months (range, 3.2–36.8 months). The overall 3-year survival rate was 83.8%. The local control rate at 3 years was 97.0% in all treated lesions. Multivariate analysis revealed that the Child-Pugh class before SBRT had significant effects on overall survival (Child-Pugh A: hazard ratio = 0.463; 95% CI, 0.262–0.817; p = 0.008). CONCLUSIONS: SBRT using a respiratory-gated VMAT technique was an excellent ablative treatment modality for patients with HCC. SBRT is a good alternative treatment for patients with small HCCs that are unsuitable for surgical resection or local ablative therapy. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12885-018-4340-7) contains supplementary material, which is available to authorized users.